Etiket Era Baru Berbasis Muatan Lokal untuk Produk Unggulan “Batik Heritage Laweyan” Siap Ekspor - Sayekti, Pranti; Irawanto, Rudi (LPkM Universitas Bakrie, 2023)
This community service activity which is carried out in the form of training aims to provide skills to Mahkota Laweyan Small and Medium Industries (IKM) in designing new era batik etiket based on local content, especially for superior products